Persepsi Konsumen terhadap Citra Merek dan Kepercayaan pada Produk Jamu Modern Tolak Angin - Baldah, Nasrun (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2026)
This study analyzes consumer perceptions of brand image and trust in the modern herbal product Tolak Angin. Based on semi-structured interviews with 10 informants, the findings show that a strong brand image and positive product experience shape favorable consumer perceptions. Trust is reinforced by social recommendations, consistent quality, and intensive marketing communication. Tolak Angin is perceived as a safe, effective, and reliable modern herbal remedy. The synergy between brand image and consumer trust drives loyalty and purchase decisions. These findings offer strategic insights for PT Sido Muncul to maintain Tolak Angin’s leadership in the herbal medicine market.